2015
DOI: 10.18632/oncotarget.3348
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide selectively targets cancer stem cells, across multiple tumor types: Implications for non-toxic cancer treatment, via “differentiation-based nano-therapy”

Abstract: Tumor-initiating cells (TICs), a.k.a. cancer stem cells (CSCs), are difficult to eradicate with conventional approaches to cancer treatment, such as chemo-therapy and radiation. As a consequence, the survival of residual CSCs is thought to drive the onset of tumor recurrence, distant metastasis, and drug-resistance, which is a significant clinical problem for the effective treatment of cancer. Thus, novel approaches to cancer therapy are needed urgently, to address this clinical need. Towards this end, here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
173
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(177 citation statements)
references
References 35 publications
3
173
1
Order By: Relevance
“…Graphene is used to detect early stage of cancer cells [77]. With the tumour sphere assay, the functionality as well as the clonal expansion of the anchorage-independent single cancer stem cell can be measured [77].…”
Section: Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene is used to detect early stage of cancer cells [77]. With the tumour sphere assay, the functionality as well as the clonal expansion of the anchorage-independent single cancer stem cell can be measured [77].…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…With the tumour sphere assay, the functionality as well as the clonal expansion of the anchorage-independent single cancer stem cell can be measured [77]. GO restricts the formation of tumour sphere effectively in various cell lines that include ovarian, pancreatic, breast, lung cancers and glioblastoma.…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…After 45 min of sonification, the stock solution (1.0 mg/mL) was diluted to different concentrations (5,10,20,50, and 100 μg/mL) with fresh 1× DMEM. Each sample was measured after 120 s of stabilization at 25°C in three replicates.…”
Section: Zeta Potential Measurementsmentioning
confidence: 99%
“…6,7 The results of experiments on various carbon nanomaterials have shown that their diverse behavior in living organisms may be useful in cancer therapy. [8][9][10][11] One of the tested materials was graphene, as previous studies have indicated that it is a very promising nanomaterial in treating glioblastoma. such as graphene oxide and reduced graphene oxide produced by chemical methods, or pristine graphene produced by physical methods, may have different properties.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, GO NPs have been proposed for treatment of cancer (5). As an evidence, Fiorillo et al revealed that GO NPs could eradicate cancer stem cells, offering them as a new therapeutic strategy of cancer (22). Moreover, when GO is co-loaded with a second anti-cancer agent, its anti-cancer properties might be improved (5).…”
mentioning
confidence: 99%